A Self-Study Action Research Approach to English for Academic Purposes - Kerekes, Julie; Zhang, Yiran; Rajendram, Shakina (The Canadian Journal of Action Research, 2024)
This study examines the effectiveness of a course for international Master’s students integrating second language acquisition (SLA) content with English for Academic Purposes (EAP) development, using a two-layered action research approach. The students in the course created self-study action research plans to achieve their EAP goals, and designed instruments to assess their progress resulting from the implementation of their plans (the first layer). The instructor also used an action research lens through which to investigate this pedagogical approach and make adjustments to the course (the second layer). The research aimed to investigate the EAP developments that students achieved through their action research plans, and the aspects of the course that contributed to those improvements. Four focal student participants' electronic portfolios were analyzed using Scarcella's (2003) academic English framework. Findings suggest that the action research model benefited students by helping them develop their linguistic, cognitive and sociocultural/psychological dimensions of academic English, and encouraging learner autonomy. Furthermore, this model benefited the instructor and her future students in terms of insights gained which allowed for improvements to the course curriculum and delivery. Implications for supporting graduate students’ EAP development and cultivating their research skills through action research are discussed.